Intention to Repurchase Tea Poci for Students of Islamic University in Bandung City - Putri, Erlina Aulia; Yuliawati, Yupi (Fakultas Ekonomi Universitas Garut, 2023)
The aim of this study was to investigate the relation between variables of distribution, customer experience, and intention to repurchase. Our population in this study was 40,644 students of Islamic universities in the city of Bandung, and the sample in this study was 400 students. The result of the analysis that has been done states that distribution, product features and community experience positively and significantly affect repurchase intentions partially and simultaneous examination states that distribution, product attributes, and community experience have a significant effect on repurchase intentions.